Re-signification of mourning and death in times of pandemic (Research, Society and Development, 2022)
Freud in his book ‘Mourning and Melancholia’ concludes that the loss of the love object puts the ego before a slow and painful work: the work of mourning. According to him, such a task takes time, thus libido shutdown needs to take place. It was formerly aimed at the lost object so that the ego becomes free to new investments. Thus, ego would be freed from a melancholic state to elaborate mourning. Consequences and changes in the perceptions of death and mourning in the COVID-19 pandemic have been investigated by means of a literature review on the Virtual Health Library (VHL) database with the following keywords: mourning, death, pandemic, and palliative care. It was followed by another literature review, this time with the keyword ‘psychoanalysis’ and without the keyword ‘palliative care’. From the theoretical framework of ‘Mourning and Melancholia’, the essay ‘On Transience’ and ‘Reflections on War and Death’, we have investigated how mourning works in times of pandemic, in which death becomes more frequent in daily life. When relating current papers to the concept proposed by Freud to analyze how the pandemic reframed the concept of mourning and death, we concluded that palliative care may help during the mourning process, identifying cases in which mourning becomes pathological and proposing multidisciplinary measures.